(untitled) - Torres, Derek (Hoboken, N.J., 2007)
Microsoft Vista may be the hot new operating system, but to use it with confidence, you'll need to know its quirks and shortcuts. Find out what the manual doesn't always tell you in this insider's guide to using Vista in the real world. How can you customize the desktop? What's the best way to prevent crashes? From setting up a home network to working with data, first get the official way, then the best way from two experts.
Keywords: Operating systems (Computers),Hệ điều hành máy tính